Optoregulated Protein Release from an Engineered Living Material. Issue 2 (17th December 2018) - Sankaran, Shrikrishnan; del Campo, Aránzazu
Abstract: Developing materials to encapsulate and deliver functional proteins inside the body is a challenging yet rewarding task for therapeutic purposes. High production costs, mostly associated with the purification process, short‐term stability in vivo, and controlled and prolonged release are major hurdles for the clinical application of protein‐based biopharmaceuticals. In an attempt to overcome these hurdles, herein, the possibility of incorporating bacteria as protein factories into a material and externally controlling protein release using optogenetics is demonstrated. By engineering bacteria to express and secrete a red fluorescent protein in response to low doses of blue light irradiation and embedding them in agarose hydrogels, living materials are fabricated capable of releasing proteins into the surrounding medium when exposed to light. These bacterial hydrogels allow spatially confined protein expression and dosed protein release over several weeks, regulated by the area and extent of light exposure. The possibility of incorporating such complex functions in a material using relatively simple material and genetic engineering strategies highlights the immense potential and versatility offered by living materials for protein‐based biopharmaceutical delivery. Abstract : An engineered living material for light‐regulated protein release is realized by combining optogenetics, bacterial protein secretion, and hydrogels. Hydrogel‐immobilized bacteria are optogenetically programmed to express and secrete a fluorescent protein in response to light irradiation. Using light, tunability and localized confinement of protein expression along with dosing of protein release are demonstrated.